Transcription Factors in the Development and Pro-Allergic Function of Mast Cells - Srivastava, Mansi; Kaplan, Mark H. (Frontiers in Allergy, 2021)
Mast cells (MCs) are innate immune cells of hematopoietic origin localized in the mucosal tissues of the body and are broadly implicated in the pathogenesis of allergic inflammation. Transcription factors have a pivotal role in the development and differentiation of mast cells in response to various microenvironmental signals encountered in the resident tissues. Understanding the regulation of mast cells by transcription factors is therefore vital for mechanistic insights into allergic diseases. In this review we summarize advances in defining the transcription factors that impact the development of mast cells throughout the body and in specific tissues, and factors that are involved in responding to the extracellular milieu. We will further describe the complex networks of factors that impact mast cell physiology and expansion during allergic inflammation and that impact functions from degranulation to cytokine secretion. As our understanding of the heterogeneity of mast cells becomes more detailed, the contribution of specific transcription factors in mast cell-dependent functions will potentially offer new pathways for therapeutic targeting.